Comparative Analysis of Operational Transconductance Amplifiers and Their Design Technologies - Simran Somal , Tripti Sharma (International Journal of Advanced Science and Technology, 2020)
This paper reviews about the various kind of operational amplifiers used for amplifying the signal orfor other applications. Nowadays, Operational amplifiers are used in all streams like electronics,electrical, medical, image processing etc. So the requirement is to make an op-amp which will able todoes all type of operations. Various kind of operational amplifiers are used like cascode amplifiers,folded cascode amplifiers, operational transconductance amplifiers etc. The basic requirement ofoperational amplifiers is it should have a high gain and low power consumption. For making thecircuit with less power consumption, various techniques are used. The basic techniques are bulkdriven technique, floating gate, input split stage, BD-MOS technique etc. The circuits which are usedby authors basically built under 180nm technology with power supply of 0.5V.